Application of Geospatial Technologies in Military Operations - OKPUVWIE, Ejuvweyere Jonathan; TOKO MOUHAMADOU, Inoussa (Socialscientia: Journal of Social Sciences and Humanities, 2023)
Geospatial technologies have made great significant difference in the world today as these technologies have wider applications in solving human problems. Globally, military operations are conducted through several methods to achieve their end state. However, over the years, some of the adopted methods most especially in developing countries have become obsolete due to the dynamic nature of the operating environment of military warfare, hence the need to adopt new technologies. The main thrust of the paper therefore is to examine the role of geospatial technologies in modern military warfare. Geospatial technologies revolve around the use of remote sensing, geographic information system, global positioning system, big data, and geospatial intelligence among others, to proffer solutions to geographic problems. The study used secondary data that were sourced from both published and unpublished works through the internet, and also applies descriptive approach. The results of the study indicated that the effective application of geospatial technologies in military operations will enables the military to effectively wage war against all forms of criminality and insurrections. The military will do better if the use of geospatial technologies is adequately applied in their operational engagement. The paper concluded that the military should train its personnel in the field of geospatial technologies in order to effectively confront the enemies of the state. The paper further recommends that personnel of the military who has received training in geospatial technologies should be deployed to the rightful departments within the military and relevant civil organizations in order to fully maximize their potentials to the benefit of the military in particular and the state at large.